The Authentic Assessment Based on Curriculum 2013 Carried by EFL Teacher - Yeni Novita Sari; Risnawati Risnawati; Zelvia Liska Afriani (Yayasan Karinosseff Muda Indonesia, 2021)
In 2013 curriculum that is a new technique to students assessment. It is know as called authentic assessment. The purpose of this study is to describe the ability of English teachers at SMAN 04 Kota Bengkulu in applying authentic assessment in classroom learning activities. This research is a descriptive qualitative research. Researcher used three instruments, namely interview, observation, and documentation in collecting data. The English teachers at SMAN 04 Kota Bengkulu are already quite good at applying authentic assessment in English learning Activities. Application of authentic, the researcher uses a table equipped with nine indicators to optimize the understanding of the teacher in learning activities in the classroom. The results of observations in the classroom indicate that the authentic assessment carried out by the teacher shows that it is quite successful, which is included in the satisfaying category. It can be said that the two English teachers at SMAN 04 Kota Bengkulu were able to fulfill and implement authentic assessment. Research suggest that authentic assessment measures should take serious care. Then English teachers really need a lot of training to make them understand better in implementing authentic assessment.